Three dimensional block-matching video denoising algorithm based on dual-domain filtering - Jin-sheng XIAO; Wen-hao LI; Hong JIANG; Hong PENG; Shen-tian ZHU (Tongxin xuebao)
The dual-domain filtering was used to remove the video noise combining with three dimensional block-matching.The correlation of time-space domain for the video sequence was fully considered.The noisy image was replaced by the result of wavelet thresholding in three dimensional block-matching video denoising algorithm as guide image,so that the base layer was smoother.Then,considering the energy spectrum of the residual matrix,the short-time Fourier transform coefficients were shrinkage which decreased the noise of the detail layer.Experimental results show that the proposed algorithm has better base layer and detail layer than the original dual-domain filtering.The subjective and objective comparison between different algorithms also proves that proposed algorithm has better denoising result.